Evaluating Adherence to Return to School and Activity Protocols in Children After Concussion. Issue 6 (November 2021) - DeMatteo, Carol A.; Lin, Chia-Yu A.; Foster, Gary; Giglia, Lucia; Thabane, Lehana; Claridge, Everett; Noseworthy, Michael D.; Hall, Geoffrey B.; Connolly, John F.
Abstract : Objective: The need to have a pediatric-specific concussion management protocol on Return to School (RTS) and Return to Activity (RTA) after concussion has been recognized internationally. The first step to evaluate the protocol effectiveness is to establish whether children and youth are adhering to these recommendations. The objective of this study was to explore the prevalence and predictors of adherence to RTS and RTA concussion management protocols for children/youth. Design: A prospective cohort of children/youth with concussion. Setting: Childhood Disability Research Centre. Participants: One hundred thirty-nine children/youth aged 5 to 18 years, diagnosed with concussion and symptomatic upon enrollment, were followed for up to 6 months. Primary recruitment occurred from a Children's Hospital Emergency Department. Intervention: Provision of RTS/RTA guidelines. Main Outcome Measures: Measurement of adherence came from multiple sources, including the child's and parent's knowledge of protocols, research personnel evaluations, and self-reported stages of RTS/RTA and Post-Concussion Symptom Scale (PCSS) scores. Results: Spearman correlations and logistic regression were used, investigating the relationship between PCSS and progression of protocols and determining predictors of adherence. Significant negative associations between total PCSS score and stage of RTS/RTA protocols were found. Fifty-three percent and 56% of the participants adhered to the RTS and RTA protocols, respectively. Conclusions: Children's knowledge of protocols and total PCSS scores significantly predicted adherence to RTS/RTA and may be the most important factors in predicting adherence during recovery from concussion. Abstract : Supplemental Digital Content is Available in the Text.